2014
DOI: 10.1038/ijos.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of riboflavin-modified, experimental, two-step etch-and-rinse dentin adhesive: Fourier transform infrared spectroscopy and micro-Raman studies

Abstract: To modify two-step experimental etch-and-rinse dentin adhesive with different concentrations of riboflavin and to study its effect on the bond strength, degree of conversion, along with resin infiltration within the demineralized dentin substrate, an experimental adhesive-system was modified with different concentrations of riboflavin (m/m, 0, 1%, 3%, 5% and 10%). Dentin surfaces were etched with 37% phosphoric acid, bonded with respective adhesives, restored with restorative composite–resin, and sectioned int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 51 publications
3
35
1
Order By: Relevance
“…21 In contrast to our findings, some studies have reported that dentin surface pretreatment with UVA-activated RF increased μTBS immediately and after storage in comparison with a control group. 9,16,21,32 The difference between our results and those of previous studies may be attributed to the duration of exposure and the source of light used for activation, as well as the storage conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…21 In contrast to our findings, some studies have reported that dentin surface pretreatment with UVA-activated RF increased μTBS immediately and after storage in comparison with a control group. 9,16,21,32 The difference between our results and those of previous studies may be attributed to the duration of exposure and the source of light used for activation, as well as the storage conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…[13][14][15] Increasing the cross-linking of collagen fibrils before applying an adhesive agent may increase bonding durability. 2,16 Despite the promising results of the application of cross-linkers, there are still some problems which need to be solved before they can be extensively used in clinical situations. For instance, glutaraldehyde is effective 13 as a collagen cross-linker, but is also toxic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Raman spectrum is considered as the tool to evaluate the structural information of hybrid layer, minute biochemical alteration and depth of resin infiltration in the hybrid layer. 17 Nevertheless, limited correlative studies were performed through microtensile bond strength, Energy Dispersive X-Ray Spectroscopy (EDX) and Micro-Raman spectroscopy. In addition, the interaction between GO and hybrid layer is still unknown despite the reported significance of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A glycidyl dimethacrylate (BisGMA) and hydroxyethyl methacrylate (HEMA) (60:40 wt%) (Sigma-Aldrich, St. Louis, MO, USA) were mixed with ethanol (30 wt%) 17 . Then, five different materials were generated with the addition of these various photoinitiators: CQ (1 mol%), CQ/PPD (0.5/0.5 mol%), CQ/BAPO (0.5/0.5 mol%), PPD (1 mol%), and BAPO (1 mol%).…”
Section: Formulation Of the Experimental Adhesive Systemsmentioning
confidence: 99%